A system perspective to the deployment of flexibility through aggregator companies in the Netherlands. (July 2018) - Lampropoulos, Ioannis; van den Broek, Machteld; van der Hoofd, Erik; Hommes, Klaas; van Sark, Wilfried
Abstract: Recent developments in distribution grids, environmental policy, and the energy market liberalisation process, have resulted in a quest for flexibility in power systems operation, with the focus increasingly placed on the aggregation of distributed resources. A generic method is proposed for the identification of opportunities, barriers and potential solutions in developing flexibility mechanisms through aggregator companies by concentrating on the market integration aspects. The method is applied to the Netherlands as a case study, and the outcome is a state-of-the-art review of the electricity market development concerning all relevant issues for advancing the market integration of aggregator companies within the Dutch system and in line with the new European grid codes. Opportunities were framed among six categories which outline the potential for the provision of market-based products and services in the Dutch system, whereas barriers were decomposed into market, regulatory, technical and social issues. A set of recommended actions is provided to facilitate the market integration of aggregator companies in the Netherlands, which point out the need for policy interventions and follow-up research activities. Highlights: We identify opportunities and barriers for flexibility services through aggregators. Market, regulatory, technical, and social barriers exist. Policy adaptations are required for the provision of operating reserves. Ensuring that energy imbalance volumes can be established beyond doubt is crucial. Smart meter data must be easily accessible to support the business models of aggregators.